2020
DOI: 10.1002/ldr.3734
|View full text |Cite
|
Sign up to set email alerts
|

Spatial differences in soil microbial diversity caused by pH ‐driven organic phosphorus mineralization

Abstract: Microbial diversity response to abiotic and biotic factors provides a sensitive indicator for estimating the potential stability and degradation of soils in agro‐ecosystems. To determine the effects of pH on organic phosphorus mineralization and microbial diversity, phospholipid fatty acid analysis, quantitative polymerase chain reaction (qPCR), and multiple ecological analyses were performed. Significant correlations were found between phosphorus components and alkaline phosphatase, phytase, and pH, between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 29 publications
8
38
1
Order By: Relevance
“…The structural equation model reflected stronger interconnections among vegetation properties, soil physicochemical properties, P-cycling-related gene abundance, cell exudates, and bacterial community composition. This result is similar to our prior finding (Wan et al, 2021a). The cooccurrence network also showed that core taxa belonging to Acidobacteria, Chloroflexi, Gemmatimonadetes, and Proteobacteria presented significant effects on vegetation properties.…”
Section: Response Of Rhizosphere Bacterial Community To Inoculation Of Strain Gp-1supporting
confidence: 91%
See 1 more Smart Citation
“…The structural equation model reflected stronger interconnections among vegetation properties, soil physicochemical properties, P-cycling-related gene abundance, cell exudates, and bacterial community composition. This result is similar to our prior finding (Wan et al, 2021a). The cooccurrence network also showed that core taxa belonging to Acidobacteria, Chloroflexi, Gemmatimonadetes, and Proteobacteria presented significant effects on vegetation properties.…”
Section: Response Of Rhizosphere Bacterial Community To Inoculation Of Strain Gp-1supporting
confidence: 91%
“…We scraped rhizosphere soils by using a brush. We measured soil physicochemical properties, including pH, total carbon, total nitrogen, and available P, based on standard methods (Wan et al, 2021a). Microbial biomass P was evaluated by chloroform fumigation extraction and was calculated as the difference between fumigated and non-fumigated subsamples and simultaneously revised for the incomplete recovery of a P spike (Roberts et al, 2013;Ragot et al, 2016).…”
Section: Determination Of Soil Physicochemical Properties Enzyme Activity and Vegetation Propertiesmentioning
confidence: 99%
“…We determined soil physicochemical properties, including electrical conductivity (EC), pH, total carbon (TC), total nitrogen (TN), NH 4 + -N, NO 3 − -N, total phosphorus (TP), available phosphorus (AP), inorganic phosphorus (IP), organic phosphorus (OP), total potassium (TK), and available potassium (AK). Detailed descriptions of determination approaches were reported in previous studies ( 37 , 61 ).…”
Section: Methodsmentioning
confidence: 99%
“…Microorganisms in wetland soils are one of the largest world reservoirs of biodiversity and drive numerous ecological processes in terrestrial ecosystems (Louca et al, 2018; Shi et al, 2018; Wagg et al, 2014). Specifically, bacteria and fungi are responsible for the turnover and cycling of important elements, including carbon, nitrogen, and phosphorus (Ge et al, 2012; Luo et al, 2018; Wan, Hao, et al, 2021). In addition, soil microbial diversity (α‐ and β‐diversity) has been shown to be closely correlated with multiple ecosystem functions, such as primary production and climate regulation (Luo et al, 2018; Wagg et al, 2014).…”
Section: Introductionmentioning
confidence: 99%